55P Incidence and clinical implications of late immune-related adverse events in long responders to PD-1/PD-L1 checkpoint inhibitors: A multicenter study. (15th December 2019) - Nigro, O; Cortellini, A; Giusti, R; Marchetti, P; De Galitiis, F; Di Pietro, F R; Bersanelli, M; Lazzarin, A; Galetta, D; Pizzutillo, P; Santini, D; Torniai, M; et al.
Abstract: Background: Immunotherapy has become a standard of care for an increasing number of tumors. Patients have a chance of developing immune-related adverse events (irAEs). In general, irAEs occur quite early, mostly within weeks to 3 months after initiation of treatment. Being drugs relatively innovative, "late" irAEs are still unknown. Methods: We conducted a multicenter retrospective study of advanced cancer patients (any histology, regardless of treatment line) treated with anti-PD-1/PD-L1 (mono)immunotherapy, with a minimum time to treatment failure (TTF) of 12 months. IrAEs were categorized into "early" (<12 months of treatment) and "late". An explorative analysis of clinical outcomes (TTF and Overall Survival – OS) was performed. Results: We evaluated 318 consecutive patients treated with immunotherapy from September 2013 to August 2018. Median age was 68.6 years (32-90). 175 patients (55.5%) experienced any grade early-irAEs, while 110 (34.6%) experienced any grade late-irAEs (p = 0.0013); 13 patients (4.1%) experienced G3/G4 early-irAEs, while 12 (3.8%) G3/G4 late-irAEs (p = 0.8446). There was a significant association between the occurrence of any grade early-irAEs and late-irAEs (p = 0.0452), as well as between G3/G4 early-irAEs and late-irAEs (p = 0.0251). Among patients who experienced early-irAEs, 63 (36%) experienced "multiple-site" irAEs (multiple sites/organs), while 17 patients (15.4%) experienced multiple-site late-irAEs (p = 0.0040). The median period of follow-up was 22.2 months. The median time to irAEs onset were 3.1 and 16.1 months for early- and late-irAEs, respectively. Late irAEs were not significantly related to TTF; on the other hand, were significantly related to a prolonged OS. When adjusted for primary tumor, late-irAEs were confirmed to be significantly related to a prolonged OS (HR = 0.25 [95%CI:0.11-0.55]; p = 0.0006). Conclusion: Late-irAEs among long responders seem to have a mild/moderate incidence. They are mostly non-serious and clinical manageable, with a low rate of treatment discontinuation. In this positive-selected population, the occurrence of any grade late-irAEs seems to be furtherly related to a prolonged OS. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.